2012
DOI: 10.1016/j.gaitpost.2011.10.359
|View full text |Cite
|
Sign up to set email alerts
|

Effects of biofeedback on secondary-task response time and postural stability in older adults

Abstract: Real-time single- and multiple-axis vibrotactile feedback of trunk motion has been shown to significantly decrease mean trunk tilt and decrease time spent outside a no vibrotactile feedback zone (dead zone) in older adults within a laboratory setting. This study aimed to determine if these improvements can translate into everyday use, during which other tasks may simultaneously demand attention. A dual-task paradigm was used in which 10 community-dwelling older adults were asked to perform standing trials in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 29 publications
4
34
0
Order By: Relevance
“…The average PEDro score for the 42 included studies was computed to be 4.7 out of 10, indicating fair quality of the overall studies. One study scored 7,36 three studies scored 6,21,35,65 20 studies scored 5,16,17,20,34,6972,74,77,7984,86,92–95 and 18 studies scored 4 22,48,61–63,6668,73,75,76,78,81,85,8789,91…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The average PEDro score for the 42 included studies was computed to be 4.7 out of 10, indicating fair quality of the overall studies. One study scored 7,36 three studies scored 6,21,35,65 20 studies scored 5,16,17,20,34,6972,74,77,7984,86,92–95 and 18 studies scored 4 22,48,61–63,6668,73,75,76,78,81,85,8789,91…”
Section: Resultsmentioning
confidence: 99%
“…Two fair-quality studies evaluated the effects of dual tasks on elderly participants 70,74. Both the studies reported a significant reduction in postural stability post dual-task intervention.…”
Section: Meta-analysis Reportmentioning
confidence: 99%
“…Such devices provide cues for directional correction of body motion with vibrating actuators placed on the torso. These cutaneous "alarm" signals triggered at predefined thresholds and historically accompanied with the instruction to "Move away from the vibration" (repulsive cuing) have been shown to significantly reduce body sway in various populations during quiet and perturbed stances (Wall and Kentala, 2005;Sienko et al, 2008Sienko et al, , 2010Bechly et al, 2012;Haggerty et al, 2012;Lee et al, 2012c). Although repulsive cuing strategies have been regularly used for such applications, they may not be congruent with kinesthetic information from the stimulated cutaneous receptors.…”
Section: Sensory Augmentation Device Applicationsmentioning
confidence: 99%
“…In general, the displays map directions of postural sway captured by a sensor with vibrating actuators around the torso. These "alarm signals" allow users to correct postural sway that would compromise balance [1][2][3][4][5][6][7][8]. When the body tilt exceeds the pre-defined threshold, one of the tactors vibrates to indicate the direction of body correction.…”
Section: Introductionmentioning
confidence: 99%
“…Wall et al [9] initially selected repulsive ("move away from the vibration") versus attractive ("move toward the vibration") cuing based on the notion that such vibrations may provoke an avoidance response similar to bumping into an obstacle. Torso-based vibrotactile biofeedback systems incorporating repulsive cuing strategies have been shown to significantly reduce body sway in individuals with vestibular deficits [3][4][5][6][7], older adults [2,8], and healthy young adults [1,3,9] during quiet and perturbed stances [4][5][6].…”
Section: Introductionmentioning
confidence: 99%